Topical Gel Loaded with Fluconazole Niosomes: Formulation and Evaluation Study - Gajjala Sravan; K. Latha; R. Padmavathi; Maimuna Fatima; C. V. Sai Sravani; M. Saritha (Challenges and Advances in Pharmaceutical Research Vol. 5, 2022)
The purpose of the study is to design and assess topical gel-loaded fluconazole niosomes. A macrolide antibiotic, fluconazole is used to treat a variety of sensitive bacteria. Niosomes can improve the penetration of drugs into the skin, and further increase the residence time of drug in the stratum corneum and epidermis, while reducing the systemic uptake of the drug. Niosomes play an important function in medication delivery because they can lower toxicity and alter pharmacokinetics and bioavailability. The investigation was conducted to confirm that the sample is a pure drug. Fourier transform infrared (FTIR 8400s, Shimadzu Japan) spectra obtained for Fluconazole (pure drug) was checked. Potassium bromide disc method was used. Optimized formulations FNS5 and FNT4 prepared with Span-60 and Tween-60 exhibited vesicle sizes of 845.6 nm and 164.2 nm, zeta potential -10.2 mV and -46.4 mV indicating the formulation has good stability. The optimized niosomes were integrated into carbopol 934 and guar gum gels and then extensively characterized for zeta potential and vesicle size. The study concluded that drug entrapment in niosomes resulted in increased drug release time, penetration, and retention.